How do you factor 6x2 - 5x - 6?

We have to factorise 6x²+5x-6

Solution

We will solve using the splitting the middle term

Multiply the coefficient of the first term by the constant 6 x -6 = -36

Find two factors of -36 whose sum equals the coefficient of the middle term, which is -5 .

The polynomial splitting the middle term using the two factors, -9 and 4 whose sum is -5 and product is -36

6x²+(9-4)x-6=0

6x²+9x-4x-6=0

3x(2x+3)-2(2x+3)=0

(2x+3)(3x-2)=0

Answer

(2x+3)(3x-2) are factors of 6x²+5x-6

Leave a Comment

Your email address will not be published. Required fields are marked *

BOOK

Free Class